High‐fidelity AFM scanning stage based on multilayer ceramic capacitors. Issue 3 (14th September 2015) - Chen, Jian; Zhang, Lian Sheng; Feng, Zhi Hua
Summary: A kind of multilayer ceramic capacitors (MLCCs) has been verified to have good micro‐actuating properties, thus making them good candidates for nano‐positioning. In this paper, we successfully employed the MLCCs as lateral scanners for a tripod scanning stage. The MLCC‐based lateral scanners display hysteresis under 1.5% and a nonlinearity less than 2% even with the simplest open‐loop voltage drive. The developed scanning stage was integrated into a commercial AFM to evaluate its imaging performance. Experimental results showed that sample images with high fidelities were obtained. SCANNING 38:184–190, 2016. © 2015 Wiley Periodicals, Inc.